Satisfaction with the Work among Tutors of Russian Higher Educational Organizations - Nelly ORLOVA; Olga RUDAKOVA; Artem TUFYAKOV (Communications of International Proceedings, 2020)
The involved staff is satisfied with the working conditions in the organization, loyal to its goals and values, and ready to take action to improve its business and organizational performance. The involvement of employees in the activities of any organization contributes to the high productivity of their work, which can have a positive effect on overall performance. The study of staff satisfaction, loyalty and involvement in higher educational institutions’ process is of particular interest. In these organizations, the role of involvement is especially great, as it lets employees identify with the educational institution, as well as form both standards for their behavior and a sense of responsibility for their implementation. The aim of the study is to analyze the level of satisfaction with the work among educators of Russian higher educational institutions. The paper assesses tutors’ involvement in comparison with other professions; the article gives analysis concerning the degree of satisfaction with the work of Russian teachers, their willingness to move to another job, preferences for wages. The results of the study indicate a relatively high level of Russian educators’ satisfaction with their work, which was proved by more than half of those teachers who were surveyed. There is a steady decline in the number of those who are ready to change jobs or stop working altogether. The share of such employees decreased from 33% in 2006 to 20% in 2017. Teachers' requirements for the level of salaries are also growing, which can stimulate their transition to another job with poor characteristics, compared to work at a university.
Keywords: Staff Satisfaction; Staff Loyalty; Staff Involvement; Human Capital; Staff Productivity; Commitment to The Profession.